A game theory analysis of green infrastructure stormwater management policies - William, Reshmina; Garg, Jugal; Stillwell, Ashlynn S. (Water resources research, 2017)
Green stormwater infrastructure has been demonstrated as an innovative water resources management approach that addresses multiple challenges facing urban environments. However, there is little consensus on what policy strategies can be used to best incentivize green infrastructure adoption by private landowners. Game theory, an analysis framework that has historically been under‐utilized within the context of stormwater management, is uniquely suited to address this policy question. We used a cooperative game theory framework to investigate the potential impacts of different policy strategies used to incentivize green infrastructure installation. The results indicate that municipal regulation leads to the greatest reduction in pollutant loading. However, the choice of the “best” regulatory approach will depend on a variety of different factors including politics and financial considerations. Large, downstream agents have a disproportionate share of bargaining power. Results also reveal that policy impacts are highly dependent on agents' spatial position within the stormwater network, leading to important questions of social equity and environmental justice. Key Points We use a cooperative game theory framework to evaluate private landowner green infrastructure implementation Regulatory, direct grant, and stormwater fee incentive strategies are evaluated, with municipal regulation leading to the greatest pollution reduction Results show that policy impacts are highly dependent on stormwater network spatial layout